Community-based participatory research with Aboriginal children and their communities: Research principles, practice and the social determinants of health - Baydala, Lola; Ruttan, Lia; Starkes, Jill (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2015)
Conventional health and social science research has contributed to advances in public well-being over the past century. Despite these advances, a significant gap exists in the health of Aboriginal children as compared to non-Aboriginal children in Canada. This has occurred, in part, as a result of the failure of conventional research to acknowledge the worldview of First Nations, Inuit, and Métis peoples, to fully take into account their experience of the social determinants of health (SDOH) and to address the intergenerational impact of colonization. In this article we review and discuss the social determinants of health (SDOH) with a specific focus on Aboriginal children and youth. Motivated by our experience in carrying out community based participatory research (CBPR) with children and families from First Nations and Métis communities in Alberta, Canada we review how use of CBPR) approach to research with Aboriginal children and communities can serve to enhance research results, resulting in greater relevance to community identified questions. We will address these issues in the context not only of good research practice but as an aspect of “wise practices” (Wesley-Esquimaux & Calliou, 2010) occurring within an “ethical space of engagement” (Ermine, 2007). We conclude that CBPR allows for meaningful and equitable research partnerships to occur in an ethical space without reinforcing colonial processes of knowledge construction and translation while marginalizing Indigenous knowledge.